The Interactions of DNA Repair, Telomere Homeostasis, and p53 Mutational Status in Solid Cancers: Risk, Prognosis, and Prediction - Vodicka, Pavel; Andera, Ladislav; Opattova, Alena; Vodickova, Ludmila (Cancers, 2021)
The disruption of genomic integrity due to the accumulation of various kinds of DNA damage, deficient DNA repair capacity, and telomere shortening constitute the hallmarks of malignant diseases. DNA damage response (DDR) is a signaling network to process DNA damage with importance for both cancer development and chemotherapy outcome. DDR represents the complex events that detect DNA lesions and activate signaling networks (cell cycle checkpoint induction, DNA repair, and induction of cell death). TP53, the guardian of the genome, governs the cell response, resulting in cell cycle arrest, DNA damage repair, apoptosis, and senescence. The mutational status of TP53 has an impact on DDR, and somatic mutations in this gene represent one of the critical events in human carcinogenesis. Telomere dysfunction in cells that lack p53-mediated surveillance of genomic integrity along with the involvement of DNA repair in telomeric DNA regions leads to genomic instability. While the role of individual players (DDR, telomere homeostasis, and TP53) in human cancers has attracted attention for some time, there is insufficient understanding of the interactions between these pathways. Since solid cancer is a complex and multifactorial disease with considerable inter- and intra-tumor heterogeneity, we mainly dedicated this review to the interactions of DNA repair, telomere homeostasis, and TP53 mutational status, in relation to (a) cancer risk, (b) cancer progression, and (c) cancer therapy.
Keywords: cancer therapy; TP53 mutational status; interactions; DNA damage response; telomere homeostasis; cancer progression; cancer risk